APOBEC3G Variants and Protection against HIV-1 Infection in Burkina Faso - Compaore, Tegwinde Rebeca; Soubeiga, Serge Theophile; Ouattara, Abdoul Karim; Obiri-Yeboah, Dorcas; Tchelougou, Damehan; Maiga, Mamoudou; Assih, Maleki; Bisseye, Cyrille; Bakouan, Didier; Compaore, Issaka Pierre; Dembele, Augustine; Martinson, Jeremy; et al. (PloS one, 2016)
Studies on host factors, particularly the APOBEC3G gene, have previously found an association with AIDS progression in some populations and against some HIV-1 strains but not others. Our study had two main objectives: firstly, to screen a population from Burkina Faso for three variants of APOBEC3G previously described, and secondly to analyze the effect of these three variants and their haplotypes on HIV-1 infection with Circulating Recombinant Forms (CRFs) present in Burkina Faso. This case control study involved 708 seropositive and seronegative individuals. Genotyping was done by the TaqMan allelic discrimination method. Minor allele frequencies of rs6001417 (p<0.05), rs8177832 (P<0.05), and rs35228531 (P<0.001) were higher in seronegative subjects. The rs6001417 and rs8177832 SNPs were associated with HIV-1 infection in an additive model (P<0.01). Furthermore the SNP rs35228531 was also associated with HIV-1 infection in a dominant model (P<0.001). Odds ratio analysis of genotypes and alleles of the different APOBEC3G variants showed that there is a strong association between the minor genetic variants, genotype of the three SNPs, and HIV-1 status. Haplotype analysis demonstrated that rs6001417, rs8177832, and rs35228531 are in linkage disequilibrium. The haplotype GGT from the rs6001417, rs8177832 and rs35228531 respectively has a protective effect OR = 0.54 [0.43-0.68] with P<0.001. There was also associations between the haplotypes GGC OR = 1.6 [1.1;-2.3] P<0.05, and CGC OR = 5.21 [2.4-11.3] P<0.001, which increase the risk of infection by HIV-1 from almost two (2) to five (5) fold. This study demonstrates an association of rs6001417, rs8177832, and rs35228531 of APOBEC3G with HIV-1 infection in a population from Burkina Faso.